The reform and development characteristics of the competition in Olympic Games - Xu, G. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction: Competition is an important component of sports. In recent years, various sports have been promoting competition reforms. This article focuses on the reform and development characteristics of the competitions in Olympic Games and Olympic Winter Games. Methods: The methods of literature review, expert interview, survey and observation have been used. Results: Competition reform is an important driving force for the sustainable development of the Olympic Games. In response to the requirements of the times, the International Olympic Committee has issued and implemented planning documents such as the Agenda 2020, New Form, and Agenda 2020+5. The relevant measures mainly involve the establishment of competition events, optimization of competition methods, and adjustment of qualification systems, etc. Firstly, the adjustment of events changes the structure of Olympic competitions and stimulate new development vitality. Based on the number of events set for the 2008 Beijing Olympics Games, the number of events in the past three Summer Olympics has increased by 8.94% (2024), 12.25% (2020), and 1.32% (2016). Based on the 2006 Olympic Winter Games, the number of events in the past three Winter Olympics increased by 29.76% (2022), 21.43% (2018), and 16.67% (2014). The number of events increased significantly in 2020 and 2014 Games. By setting up more competition events, the event structure of Olympic Games has been changed while providing athletes with more competitive opportunities and adding new competitive highlights to the Olympics. Secondly, optimizing competition methods may enrich the connotation of specialized sports. The essential difference between sports lies in the different ways athletes compete in competitions, which are mainly limited through the formulation of competition rules and the design of competition methods. In order to improve the excitement and attractiveness of competitions, managers of sports have revised and improved the specialized competition methods based on actual needs, mainly involving scoring methods, scoring standards, venue and equipment standards, etc. The specialized competition methods determine the competitive characteristics of sports and the competition scenes are more exciting and intense. Thirdly, the changes in the competition system affect the qualification for participation. In order to control the scale of Olympic events, the IOC and relevant IFs set the number of Olympic athletes (teams) based on the development level and setting of each event. The qualification system for each project determine the allocation principles, acquisition methods while the basic principle is to determine participation qualifications based on relevant important competition results. Conclusions: Competition reform is an important driving force for the sustained development of the Olympic Games. The event setting, competition methods, competition system and qualification system are the important focus points.